Botanical ingredients : the key link in Colombia for the development of innovative and natural pharmaceutical, cosmetic, and food products (2017)
ABSTRACT: otanical ingredients are widely used in food, dietary supplements, cosmetics, drugs, and other products. These ingredients may either be made as fresh material, dry and ground material, or as valorized sub-products obtained following more complex industrial process such as extraction, concentration, and purification. The plant sources of botanical ingredients are diverse. Roots, flowers, fruits, leaves, or seeds could be obtained from i) industrial crops (food and non-food); ii) wild plants (non-agroindustrial development); or iii) agroindustrial wastes (byproducts obtained during harvesting, post-harvesting, and industrial processing). Each of these sources is associated with specific challenges and advantages in the botanical ingredient industry. For example, industrial crops provide the most homogeneous raw material, but the degree of novelty and innovation in the development of these ingredients could be limited. Conversely, wild plants are the best source of novel ingredients; however, they require a lot of time and money to develop. These increased expenditures normally emerge from bioprospecting studies and legal procedures, given that the inclusion of a new ingredient is required. On the other hand, agroindustrial wastes are the most sustainable and environmentally friendly bioingredient sources; however their availability, homogeneity, and innocuousness are the most important challenges to solve.